Preferable Anesthetic Conditions for Echocardiographic Determination of Murine Cardiac Function - Yuji Kawahara; Kouichi Tanonaka; Takuya Daicho; Mikio Nawa; Ryo Oikawa; Yoshihisa Nasa; Satoshi Takeo (Elsevier, 2005)
Ketamine and xylazine are routinely used for measurement of hemodynamics of mice and rats by echocardiography. The anesthetic agents produce low heart rate (HR) in the animals, which may result in misleading data in the hemodynamic profiles of the small animals. The purpose of the present study was to select an appropriate anesthetic condition in the evaluation of mouse and rat cardiac function by echocardiography. Echocardiographic measurement was performed in male C57BL6 mice anesthetized with an intraperitoneal injection of 30 or 40 mg/kg pentobarbital (P30 or P40) or a combination of 60 mg/kg ketamine and 6 mg/kg xylazine (KX) and in male Wistar rats with an intraperitoneal injection of 40 or 50 mg/kg pentobarbital (P40 or P50) or a combination of 100 mg/kg ketamine and 10 mg/kg xylazine (KX). Basal HR of P30-anesthetized mice and P40-anesthetized were comparable to those in the conscious state, whereas KX-anesthetized mice and rats were 38% and 74% of those of the conscious animals, respectively. Fractional shortening (FS) and cardiac output index (COI) of the P30-anesthetized mice or the P40-anesthetized rats were greater than those of KX-anesthetized animals. Intraperitoneal injection of dobutamine at 0.3 and 1 mg/kg increased HR, FS, and COI of the P30-anesthetized mice and the P40-anesthetized rats, respectively, whereas the percent responses of these parameters in KX animals were greater than those in pentobarbital-anesthetized ones due to the lower basal values for the cardiac functional parameters. Anesthesia with P30 for the mouse and P40 for the rat rather than ketamine/xylazine may be relevant to the evaluation of cardiac function using echocardiography. Keywords:: anesthesia, blood flow, cardiac function, echocardiography, heart rate